North Sumatera Ethnic Gysms Training for PKK Kerapuh Village Women - Gultom, Syamsul; Samosir, Agus Salim; Ratno, Puji; Risfandi, Marsal; Raswin, Raswin (Universitas Negeri Medan, 2022)
Being fit throughout the ages is everyone's dream, excellent body fitness will allow everyone to be able to work optimally without experiencing significant fatigue. The purpose of the North Sumatera ethnic gymnastics training for PKK Kerapuh Village women, is to improve body fitness and lose weight for PKK Kerapuh Village women. This activity was carried out at the PT. Socfindo Bangun Bandar Village City. This activity was attended by 30 PKK women who are members of the gymnastics club. This activity has been able to improve the physical fitness of PKK mothers and reduce their weight by an average of 12% of their body weight. This activity has also produced 3 North Sumatera ethnic gymnastics instructors who have the ability to become Ahoy gymnastics instructors.